Mengenal Corak Tafsir Aqaid Dalam Penafsiran Al-Qur’an - Revky Oktavian Sakti; M. Yuga Fadillah (Definisi: Jurnal Agama dan Sosial Humaniora, 2023)
The interpretation of theological nuances is one of the various forms of interpretation that have existed throughout the history of interpretation (Tafsir Aqaid). a method of interpretation that unquestionably adds color to how Muslims are interpreted. To be able to see clearly and consciously in taking positive values and preventative measures against the negative aspects that are caused, it is necessary and relevant to reexamine interpretations that have a theological style. The descriptive method is used in this library-based study. The context in which the Tafsir Aqaid emerged, the aqoid interpretation's form, the School and its interpretive works, the acceptability of the Aqaid Tafsir, and examples of aqoid interpretation are the topics covered in this article. The finish of this study is The foundation The development of aqa'id translation can't be isolated from the Qur'an with the majority of understandings. The development of theological interpretation was also significantly influenced by fanaticism and political divisions. A particular theological tends to be defended, supported, and propagandized in this interpretation of aqa'id. The understanding of mu'tazilah that Allah SWT Almighty is not bound by any nature, not bound by space and time, or invisible, whereas Asy'ari says that Allah SWT is visible and grounded, and then telling mu'tazilah through his verse is really losing you mu'tazilahs if you don't understand that, is one example of the difference in interpretation of the aqoidi pattern in the concept of divinity.